Model Regresi Cox Non Proporsional Hazard dan Aplikasinya pada Data Ketahanan Hidup Pasien Penderita Tuberkulosis di Balai Besar Kesehatan Paru Masyarakat Makassar - Wahidah Sanusi; Alimuddin; Diki Nurbaldatun Islam (Journal of Mathematics, Computations and Statistics, 2018)
This type of research is applied research with a quantitative approach that is to take or collect the necessary data and analyze it by using a model of cox regression models with nonproportional hazard to determine the factors that affect the rate of recovery of tuberculosis patients in Large Hall of Pulmonary Health Makassar Society. Long treatment of patients tuberculosis is the time of survival. In accordance with the Anderson Darling test using the software Minitab 15, the test results on the distribution of survival time of tuberculosis patients is Logistic Distribution. There are many factors that will affect the rate of recovery of patients such as age of the patients, gender of the patients, smoking status of the patients, body temperature of the patients, sputum of the patients, breath of the patients, sweat of the patients, stamina of the patients, appetite of the patients, and weight of the patients. Therefore, it is important to know what the factors most affect the rate of recovery of tuberculosis patients. From the results of the research using software SPSS 20, give conclusion that factors affecting of time recovery of tuberculosis patients in Large Hall of Pulmonary Helath Makassar Society are breath of the patients, stamina of the patients, and appetite of the patients.